Consumer Perceptions and Acceptability of Traditional Dishes Prepared with Provitamin A-Biofortified Maize and Sweet Potato - Govender, Laurencia (Nutrients, 2019)
Vitamin A deficiency (VAD) is prevalent in South Africa, particularly among predominantly poor rural communities. Provitamin A (PVA)-biofortified crops could be used to address VAD; however, there are challenges of poor consumer acceptability. This study investigated the effect of replacing white maize and cream-fleshed sweet potato (CFSP) with PVA-biofortified maize and orange-fleshed sweet potato (OFSP), respectively, on consumer acceptability and perceptions of traditional dishes of rural communities in South Africa. Consumer acceptability of PVA-biofortified phutu (a crumbly maize porridge) served with either curried cabbage, chicken or bambara groundnut, separately, and boiled OFSP was evaluated by black South African adults (n = 120) using a five-point facial hedonic scale. Focus group discussions (FGDs) were conducted with 56 subjects recruited from the consumer panel to assess consumer perceptions of the food samples. The majority of the participants rated the composite dishes containing PVA-biofortified phutu as “4 = good” and the acceptability of the composite dishes varied significantly (p < 0.05). Compared to other age groups, the 50–59-year age group showed higher preference for white phutu and chicken curry, whereas the 30–39-year age group showed higher preference for PVA-biofortified phutu and chicken curry. The acceptability of OFSP and CFSP was similar. The study participants showed positive perceptions of the OFSP, as well as PVA-biofortified phutu if served with either curried chicken or cabbage. The findings suggest that PVA-biofortified maize and OFSP can replace white maize and CFSP, respectively, in selected traditional dishes of the rural communities studied to alleviate VAD.